(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Trading is one of the economic activities that is always carried out by the community. Tradingis considered to be valid if it meets the termsand pillars in Islamic law. The goods must be determined in accordance with the general provisions, so that if there is a shortage or excess of the goods, the goods must be notified to the transacting party, this is intended to guarantee and provide protection to the consumer. Plastic bag is a very effective and inexpensive storage container for consumer items. In shopping activities, sometimes these plastic bags are provided free of charge and there is no sale and purchase agreement in the transaction. The phenomenon that occurs in some X franchise retailers in Ponorogo is to give discounts on plastic bags that are not purchased by consumers, while retailers include them in the list of groceries and the plastic bags are discounted at the time of payment. This type of research uses a qualitative approach and research field as research type with observation techniques, interviews, and documentation. Researchers conducted this study to knowthe Islamic law perspective on the practice of discounting plastic bags that are not purchased by consumers. The results of research on the practice of price reduction on plastic bags provided by franchise grocery storesis not meet the termsand pillars oftransaction. Meanwhile, the price deduction in the Islamic law is basically allowed if it meets the termsand pillars for the transaction.